The Role Of Calcium In Anadara granosa Shell Graft To Osteoblast Cells In Bone Healing - Widyastuti (Denta Journal Kedokteran Gigi, 2016)
Background: Angiogenesis and osteogenesis are pairs that occur in bone healing process. Blood vessels provide oxygen. Bone is constantly being remodelled process where osteoblasts are responsible for bone formation and osteoclasts for its resorption. Osteoblast function in the process of bone formation and an early activity can be seen in reparative bone healing phase. The use of Anadara granosa shell graft in which there are more calcium, is able to provide the same inorganic component of bone, and will influence osteoblast in bone healing. Purpose: To determine the effect of application Anadara granosa shell graft with content the large of calcium on the increased amount of osteoblast in the process of bone healing. Materials and Methods: Experimental animals used in this study were 21 male Wistar rats, which were than divided into 3 groups, namely the negative control group K(-), the positive control group K(+), and the treatment group P. In the negative control group without the application of graft, in the positive control group with the application of bovine graft and in the treatment group with the application of graft Anadara granosa on the femur rats. Results: Based on the result test showed a significant differences between K(-) with K(+), K(+) with P and K(-) with P. Conclusion: Calsium in Anadara granosa shell graft application effective to increased of osteoblasts in the process of bone healing.